Effort environnemental et équité Les politiques publiques de l'eau et de la biodiversité en France - Deldrève, Valérie; Candau, Jacqueline; Noûs, Camille (EcoPolis, 2021)
This work contributes, through the notion of environmental effort, to the debate on the relationship between equity and the ef ﬁ ciency of public policies. What is the required environmental effort and what is its social distribution? What principles govern it and what feelings of justice or injustice are generated? How do the environmental policies that require this effort contribute to creating, strengthening or reducing existing social and environmental inequalities? It explores the hypothesis, inspired by the controversies present in the literature, of a higher environmental effort of the most socially vulnerable populations, regardless of their lower impact on the environment. It is put to the test of two sectoral environmental policies: that of national parks for biodiversity and those of European agri-environmental measures and Grenelle catchments for water. Selected case studies from French or overseas territories are analyzed from post-colonial, political ecology and environmental justice perspectives. They made it possible to move towards a conceptualization of the notion of environmental effort.